Evaluation of In vitro Embryo Culture and the Effect of Medium Culture, Hormone Levels and Explant Types on Callus Induction and Shoot Organogenesis of Ferula gummosa B. - R Sarabadani; M Omidi; M Bihamta; S Davazdah emami (Institue of Medicinal Plants, ACECR, 2008)
Background: Gummosa (Ferula gummosa B.) is a highly valuable medicinal plant belonging to the Apiaceae family. it is a herbaceous, perennial and monocarpic plant. Flowers appear only once during the life cycle of the plant. Objective: Our aim through present research was to reduce the long time we need for breaking seed dormancy and germination period, second was to induce healthy plantlets for preparing suitable explants for callus induction, and introducing reliable shoot organogenesis protocol by changing different media components and hormones. Method: After seed sterilization, embryonic axes were excised from the pericarp and were transferred in greenhouse with different concentrations of MS Culture Medium (MS, 1/4MS, 1/8MS), In callus induction phase, root , cotyledons, main leaf, hypocotyle, embryo and cutting embryo as a explant, were placed on MS medium with 1/4 concentration containing various combinations of plant growth regulators (PGRs), 2,4-D, NAA, BAP and kinetin. In Shoot organogenesis phase, were used B5 and 1/4MS culture medium with various combinations of growth regulators (BAP, ADS, and ABA) and viable calli from (hypocotyle, root & cutting embryo). Results: MS medium with 1/4 had the best result for seed germination and growth of seedling, The best response obtained on concentration levels of 1,2 mg/l-1 BAP and 10 mg/l-1 NAA and Root and cutting embryo were detected best explants for callus induction. The only response for shoot organogenesis was observed on 1.5 mg/l-1 BAP and 0.5 mg/l-1 ADS. Conclusion: This study showed the in vitro embryo culture could reduce the time of dormancy breaking and germination, also the effect of culture medium, explant types and hormone levels on callus induction and shoot organogenesis.